Advancing the nexus agenda for a sustainable future - McCartney, Matthew P.; Ringler, Claudia (CGIAR, 2024)
As we conclude three years of impactful work under the NEXUS Gains initiative, we reflect on the significant progress made in advancing the integration of water, energy, food, and environmental (WEFE) systems. Through collaboration with local communities, governments, NGOs, private sector, and academia, we have demonstrated how integrated solutions can enhance resilience, promote sustainability, and address some of the most pressing environmental challenges.